2011
DOI: 10.1007/s00125-011-2415-y
|View full text |Cite
|
Sign up to set email alerts
|

The endothelin receptor antagonist bosentan improves peripheral endothelial function in patients with type 2 diabetes mellitus and microalbuminuria: a randomised trial

Abstract: Aims/hypothesis Endothelial dysfunction is important in the development of vascular complications in diabetes. Patients with type 2 diabetes have increased production of the vasoconstrictor and pro-inflammatory peptide, endothelin-1. Short-term intra-arterial administration of endothelin antagonists improves endothelium-dependent vasodilatation in patients with type 2 diabetes. We tested the hypothesis that oral administration of the dual endothelin receptor antagonist, bosentan, improves peripheral endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 27 publications
(45 reference statements)
4
58
0
Order By: Relevance
“…Oral avosentan for 4 months Reduction in albuminuria, but induction of fluid overload Kohan et al (2011) Type 2 diabetes and nephropathy, n = 89 Oral atrasentan for 8 weeks Reduction in albuminuria Rafnsson et al (2012) Type 2 diabetes and microalbuminuria, n = 46 Oral bosentan for 4 weeks Improved peripheral endothelial function translocation of GLUT4 transporters and stimulation of glucose uptake (Huang et al, 2005). Phosphorylation of Akt will also directly activate eNOS leading to enhanced production of NO (Dimmeler et al, 1999;Fulton et al, 1999), to maintain normal endothelial function.…”
Section: Referencementioning
confidence: 96%
See 1 more Smart Citation
“…Oral avosentan for 4 months Reduction in albuminuria, but induction of fluid overload Kohan et al (2011) Type 2 diabetes and nephropathy, n = 89 Oral atrasentan for 8 weeks Reduction in albuminuria Rafnsson et al (2012) Type 2 diabetes and microalbuminuria, n = 46 Oral bosentan for 4 weeks Improved peripheral endothelial function translocation of GLUT4 transporters and stimulation of glucose uptake (Huang et al, 2005). Phosphorylation of Akt will also directly activate eNOS leading to enhanced production of NO (Dimmeler et al, 1999;Fulton et al, 1999), to maintain normal endothelial function.…”
Section: Referencementioning
confidence: 96%
“…Besides the aforementioned beneficial effects of ET receptor blockade following short-term intra-arterial infusions, a recent placebocontrolled double-blind study demonstrated that the dual ET A /ET B receptor antagonist bosentan improved peripheral endothelial function in patients with type-2 diabetes and microangiopathy (Rafnsson et al, 2012). The putative beneficial effect of long-term efficacy of ET receptor blockade on macro-and microvascular function in patients with type-2 diabetes mellitus is of considerable interest and should be further evaluated in additional randomized trials.…”
Section: Et-1 and Vascular Dysfunction In Insulin Resistance And Typementioning
confidence: 98%
“…88,89 Interestingly, oral treatment of 4-week duration with the dual endothelin receptor antagonist, Bosentan, improves peripheral endothelial function in patients with type 2 diabetes mellitus. 90 Finally, alteration in the mechanical properties of large compliance arteries may also fuel the pathogenesis of vascular dysfunction in diabetes mellitus. Hence, large arterial elasticity and fluid filtration across the arterial wall are impaired leading to decreased left ventriculararterial coupling in diabetes mellitus.…”
Section: Molecular Mechanisms Of Diabetes Mellitus-induced Dysfunctiomentioning
confidence: 99%
“…The study found that diabetic myocardial fibrosis was partly consequences of an activated ET system, which could lead to myocardial and vascular dysfunction (21). Unfortunately, few studies attempt to clarify the potent protective effect of bosentan, a non-selective ETa and ETb receptor antagonist, on diabetic cardiovascular complications (22).…”
Section: Discussionmentioning
confidence: 99%